Interleukin-29 Enhances Synovial Inflammation and Cartilage Degradation in Osteoarthritis - Lingxiao Xu; Qiuyue Peng; Wenhua Xuan; Xiaoke Feng; Xiangqing Kong; Miaojia Zhang; Wenfeng Tan; Meilang Xue; Fang Wang (Mediators of Inflammation)
We have recently shown that IL-29 was an important proinflammatory cytokine in pathogenesis of rheumatoid arthritis (RA). Inflammation also contributes to the pathogenesis of osteoarthritis (OA). The aim of this study was to investigate the effect and mechanism of IL-29 on cytokine production and cartilage degradation in OA. The mRNA levels of IL-29 and its specific receptor IL-28Ra in peripheral blood mononuclear cells (PBMCs) were significantly increased in OA patients when compared to healthy controls (HC). In the serum, IL-29 protein levels were higher in OA patients than those in HC. Immunohistochemistry revealed that both IL-29 and IL-28Ra were dramatically elevated in OA synovium compared to HC; synovial fibroblasts (FLS) and macrophages were the main IL-29-producing cells in OA synovium. Furthermore, recombinant IL-29 augmented the mRNA expression of IL-1β, IL-6, IL-8, and matrix-metalloproteinase-3 (MMP-3) in OA FLS and increased cartilage degradation when ex vivo OA cartilage explant was coincubated with OA FLS. Finally, in OA FLS, IL-29 dominantly activated MAPK and nuclear factor-κB (NF-κB), but not Jak-STAT and AKT signaling pathway as examined by western blot. In conclusion, IL-29 stimulates inflammation and cartilage degradation by OA FLS, indicating that this cytokine is likely involved in the pathogenesis of OA.